Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content: 1. Demographic Variables and Their Impact on Job Satisfaction Levels Among Employees of Government Units in Oman Ms. Amira Hamed Said Al-Ubaidani, Dr. Ouazzani Touhami Zineb 2. Integration between management and accounting and its role in enhancing the effectiveness of planning and control Lecturer Abadelrhem A. B. Alfageeh, Lecturer Rayad I. S. Mohamed 3. The impact of service quality dimensions on The Jordanian private medical laboratory performance Dr. Mohammed Omar Aldaaeeq,Co-Prof. Al-Harith Mohammed Abu Hussein 4. Motivation and its relationship to the performance of workers from a conceptual perspective Ms. Turkeah Salah R. Al-Hussaini 5. The Impact of Corporate Governance Mechanisms on the Quality of Financial Reporting Information: A Field Study on Some Banks and Companies in the Red Sea and Kasala States, Sudan Asst-Prof. Waleed Hussein Hassan Hussein 6. Employing the KEDA Model in Evaluating the Performance of Industrial Companies in Palestine and Jordan during 2021 - 2022 Dr. Salem Mohammad Salem, Dr. Saeid Abdelkader Zbayneh 7. Civil liability arising from the damages of cyberbullying: Towards legal protection for victims in the digital environment Mr. "Mohammad Ali" Jehad Sarah 8. The Legal Rule: Between Regulation and Obligation Mr. Ayad Kadhim Sadoon, Prof. Akram Hassan Yaghi 9. Challenges of Successful Implementation of Artificial Intelligence in Logistics Project Management at Saudi Telecom Company Dr. Norah Abdullah Al-Subaie